PKM Pemanfaatan Potensi Pangan Lokal Ubi Jalar Cilembu melalui Penepungan dan Pengolahan Mie Kering di Kabupaten Mojokerto - Chatarina Yayuk Trisnawati; Aguslina Kirtishanti; Sylvi Irawati; Ardhia Deasy rosita Dewi (GUYUB: Journal of Community Engagement, 2023)
Duyung Village, located in Trawas District, Mojokerto Regency, has local food potential for Cilembu sweet potatoes. The problem that arises is that the use of local food is not yet optimal. Processing into Cilembu sweet potato flour and dry noodles is a step to optimize its utilization. This community service activity aims to develop the local food potential of Cilembu sweet potatoes in order to achieve food security in Duyung Village. Partners for this community service activity are farmer group partners and PKK groups. Training activities on making Cilembu sweet potato flour and dry noodles made from Cilembu sweet potato flour have been able to increase partners' knowledge and skills regarding the processing of Cilembu sweet potato flour and its application in dry noodle products. Mitra is also enthusiastic about making Cilembu sweet potato flour and dry noodles which will later become a business unit. The establishment of the Cilembu sweet potato flour and dry noodle business unit is expected to increase food security in Duyung Village through utilizing local food potential